Pulmonary hypertension in infants with congenital heart defects: are leukotrienes involved? - A. Serraf; J-P. Gascard; J. Bruniaux; C. Labat; C. Planche; C. Brink (Mediators of Inflammation)
The circulating levels of leukotriene E4 in infants with congenital heart defects, increased pulmonary blood flow and pulmonary arterial hypertension, were determined and compared with infants with decreased pulmonary blood flow (Tetralogy of Fallot). There was no correlation (r=0.38) between the pulmonary arterial pressure (56 ± 4 mmHg) and the leukotriene E4 levels (1.37 ± 0.67 ng/ml blood) measured in peripheral blood samples from the hypertensive group prior to surgery. There was considerable variation in the detectable leukotriene E4 levels in blood samples from different patients. The levels detected in the blood samples between the two groups of patients was similar. These data suggest that neither the surgical repair during cardiopulmonary bypass nor the pulmonary hypertension appeared to modify the leukotriene E4 blood levels in the small number of patients studied.